Associations of glycated hemoglobin with hemoglobin levels and erythrocyte parameters - Ye.I. Dzis; O.Ya. Tomashevska; I.Ye. Dzis; N.Ya. Tomashevska (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. In patients with diabetes mellitus, pathologic changes occur in multiple organs and systems, the pathogenesis of which involves inflammatory reactions. The chronic inflammatory process can lead to the development of anemia. Several changes in red blood cells have been found to affect the processes of hemoglobin glycation, making it difficult to diagnose carbohydrate metabolism disorders. The aim of the present study was to analyze the relationship between the level of glycated hemoglobin (HbA1c) and the concentration of hemoglobin and erythrocyte parameters. Materials and methods. A complete blood count and HbA1c levels were analyzed in 756 subjects (443 women and 313 men) who underwent examination at the MeDis laboratory (Lviv) in 2020. Statistical processing of the data was performed using Student’s t, Pearson’s r, chi-square, and Fisher’s exact test. Results. Positive correlations of HbA1c with hemoglobin levels (r = 0.10, p = 0.015), neutrophil count (r = 0.08, p = 0.036), and erythrocyte sedimentation rate (ESR) (r = 0.15, p < 0.001) were found in the examined subjects. There was a negative correlation between ESR and hemoglobin levels (r = –0.42, p < 0.01). The subjects were divided into three groups according to HbA1c levels: group 1 — < 5.7 % (n = 431), group 2 — 5.7–6.4 % (n = 166), and group 3 — ≥ 6.5 % (n = 159). A positive correlation between HbA1c and hemoglobin levels was confirmed only in group 1 (r = 0.37, p < 0.001) and in women in general (r = 0.14, p = 0.002). ESR was higher in groups 2 and 3 compared to group 1 (p < 0.05). Anemia was detected in 132 (17.5 %) patients. The prevalence of hypochromic anemia was 30.0, 66.7, and 58.1 % in groups 1, 2, and 3, respectively (p = 0.001). Mean corpuscular hemoglobin was lower in group 3 compared to group 1 (p = 0.028). In all 100 women with anemia, there was a negative correlation between HbA1c and hemoglobin levels (r = –0.24, p = 0.016), mean corpuscular volume (r = –0.34, p = 0.001), and mean corpuscular hemoglobin (r = –0.31, p = 0.002). Conclusions. An increase in HbA1c is associated with increased signs of systemic inflammatory response and the development of hypochromic anemia. HbA1c and hemoglobin levels are inversely correlated with each other depending on gender, glycemic status, and the presence of anemia.